2011
DOI: 10.3324/haematol.2010.036277
|View full text |Cite
|
Sign up to set email alerts
|

Indolent mantle cell leukemia: a clinicopathological variant characterized by isolated lymphocytosis, interstitial bone marrow involvement, kappa light chain restriction, and good prognosis

Abstract: BackgroundCases of mantle cell lymphoma with indolent behavior have been reported, but are poorly identified by current clinical risk models. Early studies found peripheral blood involvement to be an adverse prognostic factor; however, cases of a seemingly indolent variant of mantle cell lymphoma, characterized by peripheral blood involvement and minimal nodal disease, have been incompletely described, particularly with regard to bone marrow findings. We report a series of leukemic phase mantle cell lymphomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(89 citation statements)
references
References 26 publications
6
83
0
Order By: Relevance
“…[2][3][4][5][6] The potential implication of SOX11 in the aggressive behavior of mantle cell lymphoma was initially suggested when it was recognized as one of the genes highly expressed in tumors requiring treatment at diagnosis compared with cases with a very indolent clinical course. 7 The relationship between the absence of SOX11 expression and an indolent clinical behavior of these tumors has been confirmed in subsequent studies [8][9][10] but not in others. 11 However, most aggressive SOX11-negative mantle cell lymphoma carry also TP53 mutations and may, therefore, correspond to a transformed form of these tumors.…”
mentioning
confidence: 54%
“…[2][3][4][5][6] The potential implication of SOX11 in the aggressive behavior of mantle cell lymphoma was initially suggested when it was recognized as one of the genes highly expressed in tumors requiring treatment at diagnosis compared with cases with a very indolent clinical course. 7 The relationship between the absence of SOX11 expression and an indolent clinical behavior of these tumors has been confirmed in subsequent studies [8][9][10] but not in others. 11 However, most aggressive SOX11-negative mantle cell lymphoma carry also TP53 mutations and may, therefore, correspond to a transformed form of these tumors.…”
mentioning
confidence: 54%
“…The kappa group had an OS of 97 months (95% CI 51Á1-142Á8) and the lambda 25 months (95% CI 12Á5-37Á5) (Log Rank: P = 0Á045) (Fig 1). Surface light chain has not been previously studied as a prognostic factor, but is known that patients with indolent MCL have a predominance of kappa light chain restriction (Ondrejka et al, 2011); in fact 3 of the four patients with indolent disease in our study showed kappa LCR. When we excluded patients with indolent disease, the prognostic impact of LCR on OS remained (kappa: median 91 months, 95% CI 61Á62-120Á37; lambda: 20 months, 95% CI 7Á92-32Á07; Log Rank P = 0Á039).…”
mentioning
confidence: 68%
“…The use of this marker, together with other clinical (non-nodal presentation) and biological features (absence of genomic complexity and 17p/TP53 alterations), may be useful to recognize this particular subgroup of MCL. 51,52,71 Microarray studies in malignant lymphomas have provided new and robust prognostic information that improves the current prognostic indices mainly based on clinical criteria, such as the International Prognostic Index (IPI). Interestingly, the GEP-based prognostic models are different for each disease entity, suggesting that the behavior of each lymphoma is determined by different mechanisms.…”
Section: Identification Of New Biomarkers and Prognostic Modelsmentioning
confidence: 99%